Pulmonary megakaryocytes: "missing link" between cardiovascular and respiratory disease?. Issue 9 (September 1986) - Sharma, G K; Talbot, I C
Abstract : Pulmonary megakaryocytes were quantitated in a series of 30 consecutive hospital necropsies using a two stage immunoperoxidase stain for factor VIII related antigen. In all 30 cases they were found with a mean density of 14.65 megakaryocytes/cm2 in lung sections of 5 micron in thickness. The maximum concentration of intrapulmonary megakaryocytes was consistently found to be in the central zone of the right upper lobe. Less than 22% of the observed cells possessed abundant cytoplasm, the rest appearing as effete, naked, and seminaked nuclei. The mean megakaryocyte count was found to be increased in association with both respiratory pathology (positive smoking history and impaired lung function) and cardiovascular disease states–shock; thromboembolism; myocardial infarction; and severe atheroma in the abdominal aorta, the coronary circulation, and the circle of Willis. Pulmonary megakaryocytes probably embolise from bone marrow. This may reflect stimulated thrombopoiesis, caused by increased platelet consumption in association with atherosclerotic disease, but it cannot be taken to confirm that the lung is the principal site of platelet production.